Effects of pyruvate on primary metabolism and product quality for a high‐density perfusion process. Issue 4 (23rd January 2022) - Caso, Stefania; Aeby, Mathieu; Jordan, Martin; Guillot, Raphael; Bielser, Jean‐Marc
Abstract: High volumetric productivities can be achieved when perfusion processes are operated at high cell densities. Yet it is fairly challenging to keep high cell density cultures in a steady state over an extended period. Aiming for robust processes, cultures were operated at a constant biomass specific perfusion rate (BSPR) in this study. The cell density was monitored with a capacitance probe and a continuous bleed maintained the targeted viable cell volume. Despite our tightly controlled BSPR, a gradual accumulation of ammonium and changes in cell diameter were observed during the production phase for three different monoclonal antibodies. Although a lot of efforts in media optimization have been made to reduce ammonium in fed‐batch process, less examples are known about how media components impact the cellular metabolism and thus the quality of monoclonal antibodies in continuous processes. In this study, we show that a continuous Na‐pyruvate feed (2 g/L/day) strongly reduced ammonium production and stabilized fucosylation, sialylation and high mannose content for three different mAbs. Abstract : For our perfusion process established for monoclonal antibodies, a gradual accumulation of ammonium and a significant change of a critical glycoform were observed during the production phase. A continuous Na‐pyruvate feed (2 g/L/day) strongly reduced ammonium production and stabilized the glycoform profile leading to a more stable overall process.